Transplanted hair follicle mesenchymal stem cells alleviated small intestinal ischemia–reperfusion injury via intrinsic and paracrine mechanisms in a rat model - Gao, Yang; Chen, Haoyuan; Cang, Xueyu; Chen, Hongliang; Di, Yuzhu; Qi, Jihan; Cai, Huimin; Luo, Kunpeng; Jin, Shizhu (Frontiers in Cell and Developmental Biology, 2022)
Background: Small intestinal ischemia-reperfusion (IR) injury is a common intestinal disease with high morbidity and mortality. Mesenchymal stem cells (MSCs) have been increasingly used in various intestinal diseases. This study aimed to evaluate the therapeutic effect of hair follicle MSCs (HFMSCs) on small intestinal IR injury. Methods: We divided Sprague–Dawley (SD) rats into three groups: the sham group, IR group and IR+HFMSCs group. A small intestinal IR injury rat model was established by clamping of the superior mesenteric artery (SMA) for 30 minutes and reperfusion for 2 hours. HFMSCs were cultured in vitro and injected into the rats through the tail vein. Seven days after treatment, the intrinsic homing and differentiation characteristics of the HFMSCs were observed by immunofluorescence and immunohistochemical staining, and the paracrine mechanism of HFMSCs was assessed by Western blotting and ELISA. Results: A small intestinal IR injury model was successfully established. HFMSCs could home to damaged sites, express PCNA and intestinal stem cell (ISC) markers, and promote small intestinal ISC marker expression. The expression levels of ANG1, VEGF and IGF1 in the IR+HFMSCs group were higher than those in the IR group. HFMSCs could prevent IR-induced apoptosis by increasing Bcl-2 expression and decreasing Bax expression. Oxidative stress level detection showed that the MDA content was decreased, while the SOD content was increased in the IR+HFMSCs group compared to the IR group. An elevated DAO level reflected the protective effect of HFMSCs on the intestinal mucosal barrier. Conclusions: HFMSCs can alleviate small intestinal IR injury through intrinsic homing to the small intestine and by differentiating into ISCs, via a paracrine mechanism to promote angiogenesis, facilitate proliferation, reduce apoptosis, regulate the oxidative stress response, and protect intestinal mucosal function. Therefore, this study suggests that HFMSCs serve as a new option for the treatment of small intestinal IR injury.